Changes in vitelline and utero-placental hemodynamics: implications for cardiovascular development - Linask, Kersti K.; Han, Mingda; Bravo-Valenzuela, Nathalie J. M. (Frontiers in Physiology, 2014)
Analyses of cardiovascular development have shown an important interplay between heart function, blood flow, and morphogenesis of heart structure during the formation of a four-chambered heart. It is known that changes in vitelline and placental blood flow seemingly contribute substantially to early cardiac hemodynamics. This suggests that in order to understand mammalian cardiac structure-hemodynamic functional relationships, blood flow from the extra-embryonic circulation needs to be taken into account and its possible impact on cardiogenesis defined. Previously published Doppler ultrasound analyses and data of utero-placental blood flow from human studies and those using the mouse model are compared to changes observed with environmental exposures that lead to cardiovascular anomalies. Use of current concepts and models related to mechanotransduction of blood flow and fluid forces may help in the future to better define the characteristics of normal and abnormal utero-placental blood flow and the changes in the biophysical parameters that may contribute to congenital heart defects. Evidence from multiple studies is discussed to provide a framework for future modeling of the impact of experimental changes in blood flow on the mouse heart during normal and abnormal cardiogenesis.